The Tanga Dairy Platform: Fostering innovations for more efficient dairy chain coordination in Tanzania - Cadilhon, Joseph J.; Ngoc Diep Pham; Maass, Brigitte L. (CentMa (Germany), 2016)
The Tanga Dairy Platform, created in 2008, is an informal forum of different stakeholders involved in the dairy industry of Tanzania’s Northeastern Tanga region. The platform’s objective is to exchange knowledge and develop joint actions to common problems. Six years on, it is a sustainable example of a commodity association addressing the joint problems of the region’s dairy industry. The platform has achieved a common understanding among chain actors on dairy price structure; it has successfully lobbied policy makers to reduce value-added tax on dairy inputs and products, and to remove limitations on urban dairy farming in Tanga city.